2017
DOI: 10.1016/j.tics.2017.09.010
|View full text |Cite|
|
Sign up to set email alerts
|

Advances in fMRI Real-Time Neurofeedback

Abstract: Functional magnetic resonance imaging (fMRI) neurofeedback is a type of biofeedback in which real-time online fMRI signals are used to self-regulate brain function. Since its advent in 2003, significant progress has been made in fMRI neurofeedback techniques. Specifically, the use of implicit protocols, external rewards, multivariate analysis, and connectivity analysis have allowed neuroscientists to explore a possible causal involvement of modified brain activity in modified behavior. These techniques have al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
211
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(227 citation statements)
references
References 69 publications
3
211
0
Order By: Relevance
“…Despite increasing interest in the application of rt- fMRI, only a few studies to date have directly evaluated effects of NFT on functional connectivity between brain regions [54, 56, 71, 76-79]. In line with the present findings, a previous study with a relatively small sample of healthy subjects revealed initial evidence for the feasibility of connectivity-informed NF which was associated with increased perception of positive valence stimuli.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Despite increasing interest in the application of rt- fMRI, only a few studies to date have directly evaluated effects of NFT on functional connectivity between brain regions [54, 56, 71, 76-79]. In line with the present findings, a previous study with a relatively small sample of healthy subjects revealed initial evidence for the feasibility of connectivity-informed NF which was associated with increased perception of positive valence stimuli.…”
Section: Discussionsupporting
confidence: 88%
“…Findings may reflect that subjects explored different regulation strategies during the initial 2 runs and maintained the successful strategies during the subsequent training runs. This difference to BOLD activity NFT studies may be explained by the fact that the functional connectivity feedback signal inherently comes at a longer delay and involves higher dimensionality [71, 72], which may lead to a higher difficulty for the subjects to discover successful regulation strategies. Future studies may increase the number of training runs and sessions to determine whether regulatory control on the neural level can be further increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As knowledge of brain structure and dynamics dramatically progresses, neuroscientists approach a stage wherein the brain cannot only be described but also be acted upon in increasingly controlled, and even constructive and enhancing fashions (Bassett & Sporns, ; Deca & Koene, ; Medaglia, Zurn, Sinnott‐Armstrong, & Bassett, ; Sahakian et al., ; Sitaram et al., ; Watanabe, Sasaki, Shibata, & Kawato, ).…”
Section: Introductionmentioning
confidence: 99%
“…One way to tackle this is to use machine learning and deep learning methods, and a number of studies have shown how this can be used to successfully build biomarkers (i.e. classifiers) in a range of psychiatric disease ( Takagi et al , 2017; Watanabe et al , 2017; Yahata et al , 2016; Yamada et al , 2017). However, these methods need to be validated on genuinely independent data sets to be convincing, and current evidence of generalisable classifiers for chronic pain is lacking.…”
Section: Introductionmentioning
confidence: 99%